LITERATURE STUDY: STUDENTS’ LEARNING MOTIVATION, ACTIVITY, AND RESULT IN LEARNING USING AUDIOVISUAL MEDIA OF HUMAN LOCOMOTION SYSTEM - Rohmat Kukuh Prabowo; Nur Kuswanti (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2022)
Media is one of important aspects in learning. This study aimed to describe students’ learning motivation, activity and outcomes in and after learning using audiovisual media on the subject of human locomotion system. This was a qualitative research using literature study method. It used secondary data derived from previous researches, i.e. development, experimental and class action researches. The data obtained showed that there was relationship among motivation, activities and student learning outcomes during and after learning human locomotion system using audiovisual media, with higher results in the experimental classes or those treated with applying audiovisual media.